The interpretation of the contemporaries about the causes of Cabanagem and the role of the parliament - Machado, André Roberto de A. (Revista de História, 2016)
The objective of this article is to highlight interpretations on the causes of Cabanagem made by contemporaries of that revolt. The text demonstrates that many of those interpretations pointed the actions of the Parliament among the reasons of the revolt. The parliamentarians themselves judged that the limits of their actions, either to integrate the province or to give them larger autonomy, precipitated the revolt in Pará. It is also rescued interpretations that did not make a direct association with the Parliament, as the idea that Cabanagem was a war of races. However, it is demonstrated that behind a supposed “war of races” was the tension around the regulation of the natives’ work in the province, theme in which the actions and omissions of the deputies and senators had utmost importance.